Ovarian cancer—can intraperitoneal therapy be regarded as new standard in Germany?. Issue 5 (1st September 2006) - Du Bois, A.; Schmalfeldt, B.; Meier, W.; Sehouli, J.; Pfisterer, J.; ,
Abstract : The German Arbeitsgemeinschaft Gynaekologische Onkologie (AGO) and the two German cooperative study groups (AGO-OVAR and NOGGO) performed a review of the currently available literature on intraperitoneal first-line treatment in advanced ovarian cancer to consider if this new option should be incorporated into the German guidelines for treatment of ovarian cancer.